CYTOTOXIC AND CHROMOTOXIC EFFECTS OF CRUDE EXTRACT OF BOTTLE GOURD IN Vicia faba ROOT MERITEM CELLS - ARUN KUMAR CHOUDHARY,; ANAND MOHAN JHA, (International Journal of Pharma and Bio Sciences, 2014)
In the present investigation cytotoxic and chromotoxic effects of crude extract of bottle gourd was evaluated by employing Vicia faba root meristem assay. Roots of Vicia faba were treated with 100, 250 and 500 g/L solution of crude extract at room temperature in dark for 6, 12, 18 and 24 h. Cytotoxicity and chromotoxicity were expressed in terms of depression in mitotic activity and frequency of abnormality in dividing cells in different phases of mitotic cycle respectively. Treatment of roots with the crude extract resulted in concentration and period of treatment dependent depression in mitotic index and increase in the frequency of abnormal cells in root tips. The result shows that crude extract of bottle gourd induced cytotoxic and chromotoxic effects in the root tip cells which may be due to the presence of residues of pesticides.